2003
DOI: 10.1046/j.1463-1326.2003.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Sibutramine enhances insulin sensitivity ameliorating metabolic parameters in a double‐blind, randomized, placebo‐controlled trial

Abstract: Sibutramine has demonstrated efficacy in reducing weight in non-diabetic women along with amelioration in insulin sensitivity and additional improvement in metabolic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Body weight and body fat distribution Mean age was 23.5 ± 1.1 (range [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Figure 2), but this difference disappeared at the end of the run-in period (S, 87.6 ± 2.2 kg; D, 83.6 ± 3.8 kg; P ¼ 0.34). Percent change in body weight at the end of run-in period did not differ between groups (S, À5.3 ± 0.3%; D, À5.0 ± 0.4%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Body weight and body fat distribution Mean age was 23.5 ± 1.1 (range [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Figure 2), but this difference disappeared at the end of the run-in period (S, 87.6 ± 2.2 kg; D, 83.6 ± 3.8 kg; P ¼ 0.34). Percent change in body weight at the end of run-in period did not differ between groups (S, À5.3 ± 0.3%; D, À5.0 ± 0.4%).…”
Section: Resultsmentioning
confidence: 99%
“…The improvement in IR with sibutramine is in accordance with other studies. 24,33,34 It is difficult to speculate on the effect of sibutramine on IR. Central obesity and in particular the amount of visceral fat is associated with IR in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Hung et al (28) demonstrated that sibutramine treatment effectively reduced weight and enhanced insulin sensitivity without an alteration in serum adiponectin concentrations in obese type 2 diabetic patients. In other study, Tambascia et al (15) suggested that 6 months sibutramine treatment was effective in improving of HOMA-IR with no change in fibrinogen levels in the non-diabetic women. In the present study, mean levels of HOMA-IR in the obese did not change with 10 mg and 15 mg sibutramine treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Elevated circulating levels of cytokines and inflammatory markers, such as interleukin-6 (IL-6), C-reactive protein (hsCRP) and tumor necrosis factor-alpha (TNF-α) have been implicated to play role in the obesity (16,19,21,22). Previous studies demonstrated that sustained weight loss was associated with reduction of cytokines (23,24) and improved insulin sensitivity (15,28). Marfella et al (25) suggested that mean levels of TNF-α and hsCRP were decreased in obese women that lost at least 10% of their original weight, after 1 year of a multidisciplinary program of weight reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, did not confirm this finding but demonstrated that the improvement in IR by the drug was dependent on weight reduction per se. 71,72 Until now, a direct action of sibutramine on IR is not proven.…”
Section: Sibutramine and Cardiometabolic Risk Factorsmentioning
confidence: 99%